On the feasibility of absolute 3D dosimetry using LiF thermoluminescence detectors and polymer gels on a 0.35T MR-LINAC - Schwahofer, Andrea; Mann, Philipp; Renkamp, Claudia Katharina; Karger, Christian (Physics in medicine and biology, 2020)
Background and Purpose. As shown in our previous study, highly accurate absolute dosimetry in 3D is feasible by combining polymer gels (PG) with thermoluminescence dosimetry (TLD). In this setup, the thermoluminescence (TL)-based point dose information is used to renormalize the PG. This new PG-TLD reference system is now extended to measurements in magnetic fields. Materials and Methods. Experiments were carried out on a conventional 6 MV linear accelerator (LINAC) and a 6 MV 0.35 T magnetic resonance (MR)-LINAC. Signal stability of TLD600 and TLD700 was examined without and with magnetic field. Afterwards, the combination of PAGAT PG and TL detectors was employed within a cylindrical phantom in presence of the magnetic field. Two scenarios were tested: (I) an air-filled phantom and (II) a water-filled phantom. For each scenario, two plans were irradiated: (a) opposed beams with a field size of 10 × 10 cm2 and (b) a 3D conformal plan assuring homogeneous target coverage using three equally distributed coplanar beams. Results. Mean relative uncertainty of TL calibration reproducibility for TLD600/TLD700 was 0.49%/0.85% at the MR-LINAC and 0.48%/0.83% for the conventional LINAC. Individual TL calibration coefficients of TLD600 and TLD700 behaved differently in the presence of the magnetic field. An average difference of (3.29 ± 0.89)% occurred for all TLD600, whereas the result for TLD700 is not quite as clear with (1.09 ± 0.89)% after excluding some outliers. Using the TL dose information for PG renormalization, high 3D gamma passing rates were achieved using the 3%/2 mm criteria: 91.0% (Ia), 92.6% (Ib), 94.3% (IIa), 97.4% (IIb). Conclusion. This study shows that TL signal reproducibility is not affected by a low magnetic field. Nevertheless, absolute calibration coefficients of the individual detectors indicate a dependency on the magnetic field. Hence, a calibration at the appropriate LINAC type is recommended. Furthermore, the previously established renormalization method for PG was applied to measurements at a MR-LINAC and was verified as suitable for evaluations of homogeneous dose distribution in the target volume.
Gesehen am 24.11.2020